2016
DOI: 10.1002/acr.22793
|View full text |Cite
|
Sign up to set email alerts
|

Further Simplification of the Simple Erosion Narrowing Score With Item Response Theory Methodology

Abstract: Objective. To further simplify the simple erosion narrowing score (SENS) by removing scored areas that contribute the least to its measurement precision according to analysis based on item response theory (IRT) and to compare the measurement performance of the simplified version to the original. Methods. Baseline and 18-month data of the Combinatietherapie Bij Reumatoide Artritis (COBRA) trial were modeled using longitudinal IRT methodology. Measurement precision was evaluated across different levels of struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…These results are in keeping with previous papers where a different method to evaluate joint involvement such as the van der Heijdemodified Sharp erosion score (SvdH) was used [29,30]. The simplified version of the radiologic scores used here has been validated in previous studies [31,32] and their validity is further confirmed in our study. Regarding the other RA-related autoantibodies, we were not able to find any association between anti-PAD3 levels and joint damage, at variance from what has previously been reported by others [23,33], despite the similar cross-sectional approach.…”
Section: Discussionsupporting
confidence: 90%
“…These results are in keeping with previous papers where a different method to evaluate joint involvement such as the van der Heijdemodified Sharp erosion score (SvdH) was used [29,30]. The simplified version of the radiologic scores used here has been validated in previous studies [31,32] and their validity is further confirmed in our study. Regarding the other RA-related autoantibodies, we were not able to find any association between anti-PAD3 levels and joint damage, at variance from what has previously been reported by others [23,33], despite the similar cross-sectional approach.…”
Section: Discussionsupporting
confidence: 90%
“…We may need to explore other approaches than the various efforts to copy the SHS measures of wrist damage. This also raises the question "which joints can reliably and consistently provide information when the goal is to assess long-term 26 Further research and development of automated assessment of joint damage help to solve these issues.…”
Section: Discussionmentioning
confidence: 99%